Respuesta :

Answer:

(x + 2)(3x + 4)

Step-by-step explanation:

3x² + 10x + 8

consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 3 × 8 = 24 and sum = + 10

the factors are + 6 and + 4

use these factors to split the x- term

3x² + 6x + 4x + 8 ( factor first/second and third/fourth terms )

= 3x(x + 2) + 4(x + 2) ← factor out (x + 2) from each term

= (x + 2)(3x + 4) ← in factored form

[tex]\\ \rm\Rrightarrow 3x^2+10x+8[/tex]

[tex]\\ \rm\Rrightarrow 3x^2+6x+4x+8[/tex]

[tex]\\ \rm\Rrightarrow 3x(x+2)+4(x+2)[/tex]

[tex]\\ \rm\Rrightarrow (3x+4)(x+2)[/tex]

Done!